Effect of Omega-3 Fatty Acid Supplementation on the Delayed-Onset Muscle Soreness (DOMS) and Inflammatory Response among Athletes and Non-Athletes - Mesta, Krishna; Medithi, Srujana (Current Nutrition & Food Science, 2023)
Background: Nutrition plays a vital role in fuelling an athlete for any sports event. The proper nutrition helps in better performance and better recovery of an athlete. Nutraceutical omega-3 fatty acids have shown to have a potential contribution to their performance output, recovery, and health/injury risk. Objective: The study aims to understand omega-3 fatty acid supplementation and review the required dose and duration of the intervention sufficient to confer any potential health benefit. Methods: The review was carried out using Google Scholar and PubMed databases. Studies were selected based on omega-3 fatty acid supplementation to improve muscle functioning and inflammation. In contrast, those studies based on animal models, pregnant women, or review articles were excluded from this review. Studies among athletes and non-athletes were selected and categorised. Results: Omega-3 fatty acid supplementation among athletes has provided substantial evidence of their health benefits in peripheral neuromuscular conditions, anaerobic endurance, muscle soreness, and reduced inflammation. It also hinted at the possible beneficial role of omega-3 fatty acid in supplementation and other sports beverages to help muscle health. Among non-athletes, it was observed that omega-3 fatty acids also help decrease the levels of inflammatory markers among non-athletes, and it helps improve muscle soreness after intense physical activity. Besides, it helps prevent muscle disuse atrophy, which could help injured individuals. Conclusion: The dose range of 1.1 g to 7 g for 2 weeks to 4 months can be effective for individuals, whether athletes or non-athletes.
Keywords: supplementation